2017
DOI: 10.5194/bg-14-5595-2017
|View full text |Cite
|
Sign up to set email alerts
|

Continuous measurement of air–water gas exchange by underwater eddy covariance

Abstract: Abstract. Exchange of gases, such as O 2 , CO 2 , and CH 4 , over the air-water interface is an important component in aquatic ecosystem studies, but exchange rates are typically measured or estimated with substantial uncertainties. This diminishes the precision of common ecosystem assessments associated with gas exchanges such as primary production, respiration, and greenhouse gas emission. Here, we used the aquatic eddy covariance technique -originally developed for benthic O 2 flux measurements -right below… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 50 publications
(59 reference statements)
1
34
1
Order By: Relevance
“…The time lag caused by the 30 mm horizontal distance between flow and oxygen measurement locations were corrected according to Berg et al (2015) through applying time shift corrections that yielded the most negative (night) or most positive (day) cross-correlations of the oxygen fluctuation and vertical movement. Oxygen fluxes then were calculated by averaging the product of instantaneous oxygen fluctuation and instantaneous vertical velocity change over time: (Berg et al, 2003). At our measuring height of 35 cm above the seafloor, the diurnal fluctuation in mean water column oxygen concentration can result in substantial changes in the oxygen inventory of the water column below the measuring volume, which can bias the local eddy flux measurements.…”
Section: Data Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…The time lag caused by the 30 mm horizontal distance between flow and oxygen measurement locations were corrected according to Berg et al (2015) through applying time shift corrections that yielded the most negative (night) or most positive (day) cross-correlations of the oxygen fluctuation and vertical movement. Oxygen fluxes then were calculated by averaging the product of instantaneous oxygen fluctuation and instantaneous vertical velocity change over time: (Berg et al, 2003). At our measuring height of 35 cm above the seafloor, the diurnal fluctuation in mean water column oxygen concentration can result in substantial changes in the oxygen inventory of the water column below the measuring volume, which can bias the local eddy flux measurements.…”
Section: Data Processingmentioning
confidence: 99%
“…This technique derives vertical oxygen flux from time series of rapid simultaneous measurements of vertical flow velocity changes and associated oxygen changes at a fixed point above the sediment surface. Since its introduction by Berg et al (2003), the strength of this non-invasive technique has been demonstrated in marine and freshwater settings (Berg et al, 2013;Chipman et al, 2016;Hume et al, 2011;Reimers et al, 2012;Rheuban et al, 2014a;Lorrai et al, 2010;Attard et al, 2019; including environments (e.g. permeable sediments, seagrass beds, coral reefs, hard bottoms, sea ice) that pose challenges to other flux-measuring techniques (Berg et al, 2009(Berg et al, , 2020Brand et al, 2008;Crusius et al, 2008;Glud et al, 2010;McGinnis et al, 2014;Long et al, 2013;Long et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Temperature dynamics, however, may affect gas exchange without any detectable changes in bulk O 2 concentrations in the water, as recently proposed by Berg and Pace (). The authors applied the same AEC approach as in this study, but in an “upside‐down” configuration, with AEC measurements being performed near the (underside) of the stream surface (~ 5 cm below the atmosphere–water interface), rather than near the streambed.…”
Section: Assessmentmentioning
confidence: 67%
“…Although k variability on short timescales, i.e., hours, has been reported (e.g., Tobias et al ; Berg and Pace ), direct and indirect methods mostly focus on determining a mean value for k 2 for either the day or night, or an average for the whole day‐night period, with little consideration being given to its short‐term dynamics that are characteristic of most rivers. Recent application of the aquatic eddy co‐variance technique (AEC) in rivers has provided robust assessment of reach‐scale (~ 150 m) benthic metabolism (Koopmans and Berg ; Rovelli et al ) and, most recently, an “inverted” AEC approach has been used to directly quantify O 2 gas exchange in large (order 3) streams (Berg and Pace ) and in an estuarine embayment (Long and Nicholson ). Yet, irrespective of the approach being applied to assess k , little emphasis has been given to small headwaters streams (order 1–2), despite their potential implications for the regional and global carbon cycling (e.g., Butman and Raymond ; Raymond et al ).…”
mentioning
confidence: 99%
“…Regionally and locally, gas transport across the air-water interface is used as a water quality index (e.g., dissolved oxygen and aeration rates) and is often needed when determining evasion rates of volatile pollutants from lakes, estuaries, or even large water treatment plants (Chu & Jirka, 2003;Frost & Upstill-Goddard, 1999;Koopmans & Berg, 2015;Liss et al, 2014;Prata et al, 2017). Given their RESEARCH ARTICLE 10.1029/2018WR022731 significance to ecosystem metabolism and uncertainty associated with model formulations (Genereux & Hemond, 1992;Marx et al, 2017;Raymond & Cole, 2001), studies on air-water gas transport in streams and rivers are now experiencing a renaissance partly driven by the rapid advancements in miniature eddy-covariance sensors (Berg & Pace, 2017).…”
Section: Introductionmentioning
confidence: 99%